2013
DOI: 10.1073/pnas.1305923110
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage adhering to mucus provide a non–host-derived immunity

Abstract: Mucosal surfaces are a main entry point for pathogens and the principal sites of defense against infection. Both bacteria and phage are associated with this mucus. Here we show that phageto-bacteria ratios were increased, relative to the adjacent environment, on all mucosal surfaces sampled, ranging from cnidarians to humans. In vitro studies of tissue culture cells with and without surface mucus demonstrated that this increase in phage abundance is mucus dependent and protects the underlying epithelium from b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
738
1
13

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 768 publications
(765 citation statements)
references
References 72 publications
13
738
1
13
Order By: Relevance
“…Our initial BAM model proposed that the enrichment of phages in mucosal surfaces depended on the binding of the Ig-like Hoc proteins exposed on T4 phage capsids to mucin glycans (11). Thus, the difference in antimicrobial effect observed here might be a result of T4 phage accumulating to a higher abundance or persisting longer within the mucus layer.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…Our initial BAM model proposed that the enrichment of phages in mucosal surfaces depended on the binding of the Ig-like Hoc proteins exposed on T4 phage capsids to mucin glycans (11). Thus, the difference in antimicrobial effect observed here might be a result of T4 phage accumulating to a higher abundance or persisting longer within the mucus layer.…”
Section: Resultsmentioning
confidence: 85%
“…Subsequently, we demonstrated that the Hoc proteins exposed on the T4 capsid bind to the mucin glycoproteins (11). The Hoc-bearing phages were enriched in mucus, reduced the bacterial load, and protected the underlying epithelial cells from infection, effects that we attributed to the putative mucin-binding activity of the Hoc protein (11). However, T4 and T4Δhoc phage particles also carry different capsid charges, as evidenced by their different electrophoretic mobilities (38).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hypervariable domains, including C-type lectins, have been identified in gut-associated phages (15), suggesting that extracellular sequestration with binding to mucus or epithelial cell surface glycans could represent another potential mechanism. Barr et al found that enrichment of phages in mucus occurs through binding of Ig-like domains exposed on phage capsids to carbohydrate residues present in the mucin glycoprotein component of mucus, thereby creating a form of antimicrobial defense that could protect mucosal surfaces (16). COPRO-Seq analysis of cecal samples obtained from mice in the germ-free treatment group that lacked the 15-member artificial community and were gavaged with the live p-VLP preparation alone revealed no detectable phages in the cecum at the time of sacrifice (Dataset S1), supporting the notion that persistence of ϕHSC03-ϕHSC05 may be dependent upon the presence of bacteria.…”
Section: Nonsimultaneous Detection Of Viruses and Community Rearrangementioning
confidence: 99%